PRESENTATION OF THE METHODOLOGY THAT HAS A PROBLEM UNDER A REFLECTION FOR SCIENTIFIC RESEARCH - Miñano Lecaros, Juan Guillermo (2014)
The application of reflective proposed methodology in a project for thesis to obtain the academic degree of master’s or doctor, must be expressed in its title, the variables to develop research, which should be confined to the problem and environment where is the problem, and that by applying epistemological and methodological tools of an objective character, can consider the alternative solution. For this, the conceptuality of the researcher should at least choose a problem that affects the governance in the plane where it operates as a professional accountant or other profession affined to Accounting, as a concept for a proposed project title research.